2020
DOI: 10.1016/j.ridd.2020.103678
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-attentional correlates of Autism Spectrum Disorder (ASD) in children with Down syndrome: A comparative study with children with idiopathic ASD

Abstract: Highlights Visuospatial orienting efficiency increases with symptom severity in idiopathic ASD. Children with Down syndrome and comorbid ASD display superior search performance. Visuo-spatial orienting ability and visual search performance appears unrelated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Although search slope (an indicator of search efficiency reflective of attentional shifting between array items and the ability to filter irrelevant items) was not associated with social functioning (ADOS Social domain), the intercept (reaction time if the visual search component was removed from the task) in the static/target present condition was negatively associated with the ADOS Social domain score. Participants in Glennon et al (2020) were required to identify a red apple embedded within an array of blue apple and red rectangle distractor targets. Although faster target detection was identified in children (both ASD and Down syndrome) with higher scores on the SRS‐2, search latency did not predict SRS‐2 scores in children with ASD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although search slope (an indicator of search efficiency reflective of attentional shifting between array items and the ability to filter irrelevant items) was not associated with social functioning (ADOS Social domain), the intercept (reaction time if the visual search component was removed from the task) in the static/target present condition was negatively associated with the ADOS Social domain score. Participants in Glennon et al (2020) were required to identify a red apple embedded within an array of blue apple and red rectangle distractor targets. Although faster target detection was identified in children (both ASD and Down syndrome) with higher scores on the SRS‐2, search latency did not predict SRS‐2 scores in children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Results were mixed. Glennon et al (2020) found that reduced facilitation (the difference in saccadic reaction time between gap and baseline trials) was associated with higher scores on the SRS‐2 in ASD. However, using auditory (rather than visual) central and peripheral stimuli, Keehn et al (2019) found that disengagement efficiency (saccadic reaction time divided by the number of trials in which a gaze shift occurred) across gap/overlap/baseline conditions was not associated with scores on the ADOS‐2 (calibrated severity score) or SRS‐2 (Total score).…”
Section: Resultsmentioning
confidence: 99%
“…Reaction times, accuracy and eye-movement data provide insight into participants’ emotion recognition abilities. ▶ Gap-Overlap task [ 74 ]: Participants view a centrally presented stimulus and then shift their attention to a peripheral stimulus presented randomly to either side. This task assesses the speed and accuracy of shifts of low-level overt attention .…”
Section: Methodsmentioning
confidence: 99%
“…The detection of co-occurring ASD among individuals with ID associated with known genetic conditions, such as DS, poses many challenges [32,33]. It is becoming increasingly apparent that individuals with DS are at increased risk for presenting with the symptoms ASD relative to the general population [5,6]; moreover, due to the developmental delays associated with the DS phenotype may influence the presentation of ASD symptomatology in this population [10][11][12].…”
Section: Discussionmentioning
confidence: 99%